Competence model scheming of the graduate as an assessment tool for the quality of education - E. N. Shaforostova; A. A. Valova (Открытое образование (Москва))
Purpose of the research. At the present time of the society development, the task of process improvement of the quality of education is especially actual and the main tool of its decision is introduction in educational process of new federal educational standards. The competences formed in the course of training, and the knowledge, abilities and skills connected with them considering social and personal qualities of learners are the main components of the developed competence model of the graduate based on new educational standards of the higher education. Therefore, the main purpose of the study is to develop methods for assessing the level of formation of competencies of students considering social and personal qualities in the framework of the developed competence model of the graduate.Materials and methods. In order to solve the research goal, the method of assessing the formation of students’ competencies within the framework of the developed competence model of the graduate was developed. The formation of the methods is based on the design of the competence-disciplinary model, which reflects the relationship of the competence model of the graduate and the corresponding educational program. Currently, there is no objective model that determines the level of complexity of tasks for each student, so in fact, approximate methods are used, which include adaptive testing. In the designed model the method of adaptive testing based on the theory of test tasks is applied. If a student correctly answers the received task, the complexity of the next task increases, if he answers incorrectly, the complexity of the task decreases. When developing a competence-based educational program a student does not begin to study the next subject, as long as he or she does not master sufficiently the discipline on which the next subject is based. To determine the necessary interdisciplinary relationships, we use a weighted semantic network, for the construction of which we form an adjacency matrix. In the formed matrix, the units are disciplines connected by arcs, which reflect the dependence of the formed competencies of one discipline with the competencies of the subsequent discipline.Results. As a result of the analysis of existing methods, the model for assessing the quality of training with the social and personal qualities was designed. The method of adaptive testing was chosen to assess the level of competence formation. The main task of adaptive testing is not just to assess a student knowledge, but also to determine the level of his training, which is possible only in the selection of individual questions, revealing the level of the training. For reliable identification of the formation level of social and personal qualities, the obtained adapted version of R Ketell’s multifactorial questionnaire was used, in which the components are the formed groups of personal qualities. The algorithms of adaptive testing to assess the level of competence of students in the development of academic disciplines, as well as the assessment of existing social and personal qualities of students were developed.Conclusion. The scientific novelty of the work is to develop a competency model of a graduate not only considering the assessment of the formation level of competencies of a student, but also considering social and personal qualities.The results of the study are relevant and have practical significance for higher education organizations to solve the problems of assessing the level of training within the competence approach.